Kinetic toys - Lee, Brian Zong Han. (2009)
The nature of this report revolves around the investigation and implementation of a simple kinetic planar structure based on articulated Bricard linkages. We explore how existing spatial overconstrained linkages with revolute joints can be fabricated and used as a kinetic planar toy. The Bricard linkages can transform between a fully closed configuration and a maximum expanded one. The kinetic structure is used as architecture for a robotic assembly. A six bar element of the basic threefold Bricard linkage is fabricated as the base structure and the links are joint together by revolute joints. The articulated structure is geometrically overconstrained, with a single degree of mobility. The links of the structures are connected to flanges so the angles of twist between the linkages can be varied to achieve the desired configuration. Therefore, the structure can be actuated to “walk” with a triangular profile. A kinetic structure is fabricated; it consists of six carbon fibre tubes that act as linkages and six joints with three contacting the ground. When actuated, two joints will slide in a planar fashion on the ground and one “locked” to the ground by means of a rubber contact pad. The successful movement of the novel structure resembles that of an inching robot and is a interactive structure; demonstrating one of the many applications for kinetic linkages. A microcontroller controls the servos which will move the robot in the desire path. It moves by timing the sequence of the friction pads contacting the ground and fine adjusting the pad positions. The structure requires a reasonable level of precision in fabrication as there is a high level of friction involved when moving. The joints experiences twist when articulating the structure and are fabricated from tough material so that it can resist wear and tear from repeated use.